Moonfleet - Falkner, J. Meade; Adapted by Warburton, Nick; Illustrated by Oldroyd, Mark (Oxford Oxford University Press, 2014)
Moonfleet tells the story of John Trenchard. One night in Moonfleet, he hears a tale of cursed treasure. John and his friend Elzevir go in search of the treasure and become involved in another Moonfleet secret smuggling. TreeTops Classics are adapted and abridged versions of classic stories to enrich and extend children's reading experiences.
Include Illustrations.
English Fiction.